Movimentos de desconstrução: a formação de professores e professoras / coordenadores e coordenadoras da educação básica - Americano, Renata Queiroz de Moraes (2019)
Can deconstruction show any evidence of the beliefs and transformations that teachers/coordinators have built throughout their story? How are they present in their educational actions? The following research goes through different paths in order to understand if teachers and coordinators have lived deconstruction moments that might have affected their beliefs about education and if they have caused any impact on their practises. For the research's development, the choice of using A/r/tography as methodology was essential to interlace with art, to understand its contribution in the process of teachers' formation with the purpose of provoking transformative experiences. Testimonials collected by e-mail were used as well as face-to-face interviews and the studies of theorists as Antônio Nóvoa, Ana Angélica Albano, Madalena Freire, Fernando Hernández, Denise Vaillant, Vea Vecchi, Peter Moss, Isabel Alarcão, Jerome Bruner e Mirian Celeste Martins. Deconstruction movements were revealed in: the relation of learning and teaching in lived experiences; Continuing Education and life on learning communities; change of management or function; creation processes in teaching. It was also confirmed the potency of art understood as a way of thinking the world, not just as a specific language, but offered as a space/studio for the expressive work that provokes deconstructions and resignifications of the pedagogical actions.